STAKEHOLDER PARTICIPATION - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
A World Conference on Multifunctional Agriculture and Land Management will be held in Den Bosch, The Netherlands, in September 1999. The organisers (The Netherlands government and FAO) wish 'to engage the widest possible representation of...